Social-Relational Model dalam Undang-undang Penyandang Disabilitas - Millati, Sofiana (PLD UIN Sunan Kalijaga, 2016)
This article aims to analyze the Law Number 8 year 2016 on the Persons with Disabilities using the Social-Relational Model of disability. The debates between Medical Model versus Social Model have developed through disability discourses in Indonesia. This research argues that the correlation between Medical Model and Social Model is not mutually exclusive, rather, it is relationally necessary. Social Relational Model influnce in the Law can be discussed within three subjects: the rights for education for the persons with disabilities, the rights for justice and legal protection, and the rights for health.[Artikel ini bertujuan untuk mengkaji Undang-Undang Nomor 8 tahun 2016 tentang Penyandang Disabilitas melalui pendekatan Sosial-Relational Model. Perdebatan antara Medical Model versus Social Model telah berkembang melalui diskursus diskursus disabilitas di Indonesia. Penelitian ini berargumen bahwa terdapat hubungan interelasional antara perspektif Medical Model dan Social Model yang sebenarnya bukan bertolak belakang, melainkan saling melengkapi satu sama lain. Dalam penelitian ini, dibahas relevansi pendekatan Social Relational dalam beberapa tema antara lain hak atas pendidikan, hak atas keadilan dan perlindungan hukum, dan hak atas kesehatan.]